Prevalence of constipation and lifestyle risk factors related to constipation in an adult population of South Tangerang - Nisa, Hoirun (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Constipation is a common bowel complaint in a general population that can negatively impact a quality of life. Unhealthy lifestyles play major roles in causing the constipation. Objective: This study was aimed to estimate prevalence of the constipation and identify lifestyle risk factors related to constipation in a general adult population. Methods: A cross-sectional survey was conducted on 227 adults aged =20 years, who lived in East Ciputat, South Tangerang. Information about demographic characteristics, lifestyle habits, and bowel habits was collected through in-person interviews. Chi-square test and logistic regression were used for data analysis. Results: The prevalence of self-reported constipation in the general adult population was 21.6%. The common symptoms included defecation time =5 minutes (39.6%), sensations of incomplete evacuation (37.9%), and frequency of defecation <1/day (34.4%). Married status was related to a decreased risk of constipation (odds ratio= 0.31; 95% confidence interval= 0.11-0.89). Lifestyle factors of smoking, sedentary job, body mass index, and physical activity were less related to the risk of constipation. Conclusion: The prevalence of constipation was relatively high in the general adult population in South Tangerang. Further studies are needed to explore the relationships between lifestyle risk factors and constipation in other populations.